The Pedicles Are Not the Densest Regions of the Lumbar Vertebrae: Implications for Bone Quality Assessment and Surgical Treatment Strategy - Hohn, Eric A. (Global Spine J, 2017)
STUDY DESIGN: Cadaver study. OBJECTIVE: To determine the bone density of lumbar vertebral anatomic subregions. Bone mineral density (BMD) is a major factor in osseous fixation construct strength. The standard region for implant fixation of the spine is the pedicle; however, other regions may be more viable options with higher bone quality. METHODS: Using computed tomography images, the spine was digitally isolated by applying a filter for adult bone. The spine model was separated into 5 lumbar vertebrae, followed by segmentation of each vertebra into 7 regions and determination of average Hounsfield units (HU). HU was converted to BMD with calibration phantoms of known BMD. RESULTS: Overall mean BMD in vertebral regions ranged from 172 to 393 mg/cm(3) with the highest and lowest BMD in the lamina and vertebral body, respectively. Vertebral regions formed 3 distinct groups (P < .03). The vertebral body and transverse processes represent one group with significantly lower BMD than other regions. Spinous process, pedicles, and superior articular processes represent a second group with moderate BMD. Finally, inferior articular process (IAP) and lamina represent a third group with significantly higher BMD than other regions. CONCLUSIONS: Standard lumbar fusion currently uses the vertebral body and pedicles as primary locations for fixation despite their relatively low BMD. Utilization of posterior elements, especially the lamina and IAP, may be advantageous as a supplement to modern constructs or the primary site for fixation, possibly mitigating construct failures due to loosening or pullout.